Implementation of Brainwriting Strategy in Improving Writing Skill at the Tenth Grade Students of MA Putri Aisyiyah Palu - Sri Sofya Nurfitri; Andi Naniwarsih; Sari Wulandari (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research intends to find out whether the brainwriting strategy can improve the writing skills of the tenth-grade students of MA Putri Aisyiyah Palu or not. The sample selected was using total sampling techniques. The researchers applied the pre-experimental design. The results of the pre-test of the mean score are 55.17. The results of the post-test of the mean score are 68. After delivering the test, the data obtained indicate an improvement in the mean score of students’ tests. The testing hypothesis is conducted to df = n-1 out whether this improvement is significant or not by comparing t-counted 10.68 to t-table 1,745 (df= 16 and ?=0,05). The result shows that the t-counted is higher than the t-table, so the hypothesis is accepted. In other words, the Brainwriting Strategy can improve students’ writing skills in tenth-grade MA Putri Aisyiyah Palu effectively.